Ideas acerca de la participación femenina en los procesos de violencia - Gallegos Martínez, Carolina (Archivos de criminología, seguridad privada y criminalística, 2021)
Regarding the crime figures that appear in Mexico impregnated with violence, it is necessary to reflect on the participation of women in this process. It usually happens that the woman is in a passive or active position, in both cases being in an unfavorable position. For this reason, this article gathers some ideas of a criminological nature in order to expose the situation of criminal women and the characteristics that today make this problematic an area of study that must be attended to in a demanding manner. The conclusions are linked to an imperative task of studying the delinquent woman showing the reality that is in force and in which she lives.